Oswajanie „śmiertelnego niebezpieczeństwa”. Rewolucja lutowa na łamach „Tygodnika Ilustrowanego” w 1917 roku: Taming “mortal danger”: The February Revolution on the pages of “Illustrated Weekly” in 1917 - Gabryś-Sławińska, Monika (Przegląd Wschodnioeuropejski, 2020)
The article aims to reconstruct the ways in which “Illustrated Weekly” informs the public about the events of the February Revolution in Russia. Additionally the article interprets public opinion held by Polish readers about the events in question. The analysis is based on the issues of the weekly published between the outbreak of the February Revolution and the Bolshevik revolutionin October 1917. The analysis includes both verbal and iconographic representation. Research has shown that the editorial board of “Illustrated Weekly” consistently avoided commenting on the reports from Russia, at the same time they replaced the current news with texts about events of 1905-1907. Their strategy of substitution and analogy indicates that the weekly and its readers could not handle the interpretation of the current political situation in Russia.